Mentoring English Learning Based on Local Linguistic and Cultural Artifacts to Enhance Basic Literacy of Islamic Boarding School Students in Underdeveloped Regions - Bincar Nasution; Sri Rahma; Rabiyatul Alawiyah; Nurkholidah Nurkholidah; Nur Latifah; Fitri Romaito Lubis (PT Inovasi Pratama Internasional, 2026)
Basic English literacy remains a critical challenge for students in underdeveloped regions, particularly for santri (Islamic boarding school students) whose curricula prioritize religious texts over foreign language skills. This qualitative study investigates the design and implementation of a community mentoring program that leverages local linguistic and cultural artifacts to foster foundational English reading, writing, and vocabulary among junior secondary santri in a remote coastal pesantren in East Nusa Tenggara, Indonesia. Employing a participatory action research design, data were gathered over sixteen weeks through participant observation, semi-structured interviews with ten santri, three mentors, and two pesantren teachers, analysis of instructional artifacts, and pre-post literacy performance assessments. The mentoring model integrated oral folklore, traditional games, local songs, and everyday objects recontextualized as English learning media. Thematic analysis revealed four interconnected improvements: (1) heightened lexical retention through tangible cultural referents; (2) increased decoding confidence when English graphemes mapped onto locally meaningful narratives; (3) emergent writing competencies scaffolded by collaborative labeling of familiar artifacts; and (4) a transformed affective stance that repositioned English from a foreign threat to a culturally congruent resource. Pre-post assessment data displayed a notable shift from non-reader to word-level decoding for all participants, with 70% advancing to simple sentence construction. The findings suggest that culturally sustaining, artifact-based mentoring can disrupt the symbolic exclusion of English in traditional pesantren while strengthening basic literacy in underserved contexts.